Modelled Energy Cost Minimization Solution for Wireless Rechargeable Sensor Networks - Musa Ahmed; Dominic Saaityo NYITAMEN; Fatai Olatunde Adunola; Sagir Lawan (ABUAD Journal of Engineering Research and Development)
In wireless rechargeable sensor networks (WRSNs), mobile chargers (MCs) are normally scheduled to deliver energy to the rechargeable sensor nodes (SNs). However, due to the energy consumption dynamicity of WRSNs, constructing optimal charging trajectories with minimized number of failed SNs due to energy deficiency ensuring a sustained WRSN operation at minimum MC’s movement cost is one aspect of the subject matter not yet thoroughly investigated. Thus, exploring this knowledge is the focus of this work. We applied shortest path algorithm, on-demand scheduling and multi-node charging methods to construct the energy cost-effective charging path for the MC, a model we coined as Shortest Hamiltonian Cycle Traveling Salesman Problem (SHC-TSP). Comparative analysis proves the optimality of our solution against the notable nearest job next with pre-emption (NJNP) model in terms of minimizing MC’s traveling energy cost with energy savings of 3.9156% and 2.1940% for the two scenarios respectively examined.